2019
DOI: 10.1002/chem.201900831
|View full text |Cite
|
Sign up to set email alerts
|

Palladium(II)‐Based Self‐Assembled Heteroleptic Coordination Architectures: A Growing Family

Abstract: Metal-driven self-assembly is one of the most effective approaches to lucidlydesign alarge range of discrete 2D and 3D coordinationa rchitectures/complexes. Palladium(II)-based self-assembled coordination architectures are usually preparedb yu sing suitable metal components, in either ap artially protected form (PdL')o rt ypical form (Pd; charges are not shown), and designed ligand components. The self-assembled moleculesp repared by using am etal component and only one type of bi-or polydentate ligand (L) can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 196 publications
0
67
0
2
Order By: Relevance
“…The cages 4a and 5a are hitherto unknown examples of heteroleptic complexes wherein ligands of different denticity are coordinated to Pd(II) 8 . Thus, the present set of cages are unique due to their structural features and associated binding properties.…”
Section: Discussionmentioning
confidence: 99%
“…The cages 4a and 5a are hitherto unknown examples of heteroleptic complexes wherein ligands of different denticity are coordinated to Pd(II) 8 . Thus, the present set of cages are unique due to their structural features and associated binding properties.…”
Section: Discussionmentioning
confidence: 99%
“…As we could not cover all so far reported studies comprehensively, we apologize for what might not have found entry into this selection and refer to further reviews in this direction. 26,[39][40][41][42][43]…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 One reason for this success, lies on the high degree of predictability in the geometry of the resulting selfassembled structures. 3 On this basis, more and more complex systems have been produced, including chiral [4][5][6] , heteroleptic [7][8][9] and interlocked [10][11][12] ones. Those self-assembled discrete structures generally include a cavity, 13 and their host properties have been widely studied to target various applications (e.g.…”
Section: Introductionmentioning
confidence: 99%